The Development of Entrepreneurship Courses for Prospective Teacher Students: Competency Analysis and Study Materials - Sukarno, Sukarno; Haryati, Sri; Siswanto, Siswanto; Trisnowati, Eli; Setiati, Farida Nur (AL-ISHLAH: Jurnal Pendidikan, 2024)
Entrepreneurship courses are one of the important courses to be developed in the curriculum of education study programs. This is to equip students, apart from having abilities in the field of education, to have an entrepreneurial spirit. Prospective teacher students need to be equipped with entrepreneurial competencies as a provision for living life after graduating from lectures as prospective teachers. Currently, there are rarely studies on the development of entrepreneurship courses for prospective teachers. This study aims to develop competencies and study materials that need to be mastered by prospective teacher students in entrepreneurship courses. This research was conducted using the delphi method involving expert consensus to determine the competencies and study materials for entrepreneurship courses. These competencies and study materials are used as the basis for developing semester learning plans (RPS) by lecturers. The results showed that there are ten competencies that must be mastered by prospective teacher students in carrying out entrepreneurship lectures. The most important thing is about exploring local potential which can be utilized for entrepreneurial activities.  The ten competencies were also analyzed based on priority order factors that must be trained to students. Through this research, it is necessary to develop a more practical curriculum for educational study programs.